Loss to follow up of failed hearing screen and missed opportunities to detect congenital cytomegalovirus are better identified with the implementation of a new electronic health record system protocol. (September 2021) - Raynor, Eileen; Holmes, Christine; Crowson, Matthew; Peskoe, Sarah; Planey, Arrianna; Lantos, Paul M.
Abstract: Introduction: Congenital CMV (cCMV) is the leading cause of non-genetic sensorineural hearing loss. Babies with cCMV can present with hearing loss any time but failing the initial hearing screen should trigger cCMV testing. cCMV must be identified within 3 weeks after birth to differentiate congenital from acquired CMV, yet follow-up hearing screens may not occur until after 21 days. A new electronic health record protocol to test cCMV in babies who fail their initial hearing screen was established at our institution in 2013. The purpose of this study is to evaluate adherence and deviations from this protocol. Methods: All term infants born in 2013–2016 who failed initial hearing screen were included. The records were reviewed retrospectively. Demographic data, dates of hearing screens, CMV testing results and follow-up hearing test results were collected. Results: A total of 19, 069 newborn babies were screened between 2013 and 2016. Babies who were in the neonatal intensive care unit whether premature or not were excluded as these infants are often in the hospital longer than 3 weeks so audiologic diagnostic testing may be delayed. Among term newborns screened, 1358 failed initial screen and 444 failed subsequent hearing testing prior to discharge. We identified 60 babies who did not follow up and 59 underwent additional audiologic testing. Overall 38 babies were tested for cCMV with 2 positives. We found an increase in cCMV testing over time and a significant decrease between physical distance from birth hospital and outpatient audiologic follow-up testing within 21 days of birth. Discussion: Our results are consistent with a 0.4% rate of cCMV in full-term babies who failed their newborn hearing screen. From 2013 to 2016, more babies received CMV tests, but post-screening follow up was still delayed. Further research is necessary to address factors affecting follow up. Use of electronic health record eased identification of results and improved tracking.